8. ANALYSIS OF THE USE OF THE SUPER MINDS PP LEVEL 3 APPLICATION FOR ENGLISH LEARNING IN READING FOR THE PURPOSE OF DEVELOPING THE CAPABILITIES OF DEFENCE EQUIPMENT MANUFACTURING ENGINEERS MEMBER - Muchammad Furqon Muchaddats; Khusnul Khotimah Nabilah; Kurniawan; Dikatama (Staf Komunikasi dan Elektronika, TNI Angkatan Udara, 2025)
The objective of this study was to analyze of using ‘Super Minds PP Level 3 Application’ in learning English reading and Defence Equipment Manufacturing Engineer Member ’ perceptions in learning English reading. The study employed the qualitative method. The objectives include some explanations about technology, how to teach Defence Equipment Manufacturing Engineer Member in reading by using ‘Super Minds PP Level 3 Application’, Defence Equipment Manufacturing Engineer Member ’ motivation of using ‘Super Minds PP Level 3 Application’ in learning English reading, giving some brief discussions about teaching strategies, teaching methods, teaching techniques, teacher preparation, and observing the video recording of the Defence Equipment Manufacturing Engineer Member ’ learning in reading by using ‘Super Minds Application PP Level 3 Application’. The research uses a qualitative approach by observing, analyzing data, and summarizing the findings. Books, journals, the English dictionary, and websites are needed to support the analysis. The result from the research, the researcher can explore the Defense Equipment Manufacturing Engineer Member ’ perceptions or assumptions based on interview questions in learning English Reading by using ‘Super Minds PP Level 3 Application’. Therefore, the researcher can understand and know the positive or good impacts and negative or not good impacts in learning English reading by using ‘Super Minds PP Level 3 Application.